SDG5 Gender Balance Progress Implementation; A Comparative Study of Romania and The Netherlands - Faragalla, Widad Atena; Cuibus , Bianca (The Journal of Accounting and Management, 2024)
Gender balance is an important vector for the wellbeing of all societies. The objective of this paper is to determine how SDG5 is applied in Romania and The Netherlands from a legislation perspective and, at the same time to understand the evolution of the implementation of SDG5 gender balance . To achieve the objective, data provided by the United Nations annual reports Sustainable development Goals for a time span of 23 years (2000 to 2023) were analyzed for the selected countries and compared to the EU average. Moreover the evolutiuon of legislation was analised in a comparative manner.Our results show that Romania is still underperforming compared to The Netherlands in many aspects but at the same time the progress can’t be denied, historically speaking. One of the values added to this paper is the cross-country comparison of the indicators based on which SDG5 is measured at EU level.